PERANCANGAN SISTEM INFORMASI REGISTRASI LOMBA PEKAN OLAHRAGA DAN SENI DENGAN PEMANFAATAN INTEGRASI PAYMENT GATEWAY DI SMAN 15 BANDAR LAMPUNG - firdhayanti, ayu; Agarina, Melda; Sutedi, Sutedi; Suryadi , Arman; Fauzi Maulana, Muh Royan (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
This research aims to design a web-based information system to facilitate the registration process for competitions in Sports and Arts Week (PORSENI) at SMAN 15 Bandar Lampung. This research was motivated by the complexity of the manual registration process that involved many participants from different schools, especially those from out of town. The designed information system integrates an online payment function through the Xendit payment gateway. This system is expected to increase the efficiency of the registration process, reduce the committee's workload, and provide convenience for participants to register and pay online. The results showed that the developed information system successfully simplified the registration and payment process of the competition. Participants can register and pay independently without coming directly to the committee. In addition, this system can automate several processes that were previously done manually, thus increasing the efficiency of the committee's work. Implementing this information system has positively contributed to the organisation of PORSENI at SMAN 15 Bandar Lampung.